The long‐term outcome of MOGAD: An observational national cohort study of 61 patients. (19th February 2021) - Deschamps, Romain; Pique, Julie; Ayrignac, Xavier; Collongues, Nicolas; Audoin, Bertrand; Zéphir, Hélène; Ciron, Jonathan; Cohen, Mikael; Aboab, Jennifer; Mathey, Guillaume; Derache, Nathalie; Laplaud, David; et al.
Abstract: Background and objective: The prognosis in myelin oligodendrocyte glycoprotein (MOG) antibody‐associated disease (MOGAD) is a matter of debate. Our aim was to assess the long‐term outcomes of patients with MOGAD. Methods: We retrospectively analysed the clinical and paraclinical data of patients from the French nationwide observatory study NOMADMUS who tested positive for MOG antibodies (MOG‐IgG) and who had clinical follow‐up of at least 8 years from their first episode. Results: Sixty‐one patients (median [range] age at onset 27 [3–69] years), with a median (mean; range) follow‐up of 177 (212.8; 98–657) months, were included. Among 58 patients with a relapsing course, 26.3% relapsed in the first year after onset. Of the 61 patients, 90.2% experienced at least one episode of optic neuritis. At last visit, the median (mean; range) Expanded Disability Status Scale (EDSS) score was 1 (2.12; 0–7.5), 12.5% had an EDSS score ≥6 and 37.5% had an EDSS score ≥3. Of 51 patients with final visual acuity (VA) data available, 15.7% had VA ≤0.1 in at least one eye and 25.5% had VA ≤0.5 in at least one eye. Bilateral blindness (VA ≤0.1) was present in 5.9% of patients. Finally, 12.5% of patients presented bladder dysfunction requiring long‐term urinary catheterization. No factor associated significantly with a final EDSS score ≥3 or with final VA ≤0.1 was found. Conclusion: Overall long‐term favourable outcomes were achieved in a majority of our patients, but severe impairment, in particular visual damage, was not uncommon. Abstract : Sixty one patients with myelin oligodendrocyte glycoprotein antibody‐associated disease were included, of whom 90.2% experienced at least one episode of optic neuritis. At last visit (median [range] follow‐up of 177 [98–657] months), the median (mean; range) Expanded Disability Status Scale (EDSS) score was 1 (2.12; 0–7.5), 12.5% had an EDSS score ≥6 and 15.7% had visual acuity (VA) ≤0.1. Bilateral blindness (VA ≤0.1) was present in 5.9% of patients. No factor was associated significantly with a final EDSS ≥3 or with final VA ≤0.1. Overall long‐term favourable outcomes were achieved in a majority of patients, but severe impairment, in particular visual damage, was not uncommon.